Eine Theorie von der Wissenschaft des Recht - Peters, Kristina; Schrott, Nina (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The question of the scientific nature of jurisprudence is often either rashly answered in the affirmative in view of its institutional anchoring and authority, or else it is understood as an academic glass bead game that leads artificial questions to a solution that may be well-founded in legal theory, but is nevertheless largely irrelevant for legal practice and society. In fact, however, what is at stake is nothing less than participation in the rationality of the sciences and their special methods of cognition. The volume therefore embarks on a search for the ontological and epistemological foundations of legal science and sketches a scientific foundation for legal methodology.With contributions byDr. Markus Abraham; Dr. Dr. Philipp-Alexander Hirsch; Dr. Jannis Lennartz; Dr. Kristian Peters; Dr. Bettina Rentsch; Dr. Nina Schrott; Dr. Rike Sinder, M.A.; Amadou Korbinian Sow and Dr. Alexander Stark.